Correlation and prognosis analysis of human papillomavirus infection and P16 expression in oral and oropharyngeal squamous cell carcinomas - Yandie Lin; Zhirui Li; Kai Zhang; Xiaoyue Li; Liwei Shao; Aijun Liu (Scientific Reports)
Abstract The incidence of HPV-related oral squamous cell carcinomas (OSCC)and oropharyngeal squamous cell carcinomas (OPSCC) has increased significantly in recent years, but the role of HPV and P16 in OSCC and OPSCC remains controversial. Here, we evaluate the prevalence and prognostic significance of HPV-DNA, HPV E6E7 and P16 protein expression in OSCC and OPSCC patients. Additionally, we explore the correlation between P16 protein expression and HPV infection in these cases. The results show that the HPV DNA infection rate was significantly higher in OPSCC at 16.7% compared to 3.6% in OSCC (P = 0.002), HPV DNA positive cases were more prevalent in poorly- differentiated cases (P = 0.009). HPV E6E7 positive cases (10.4%) were only detected in OPSCC. P16 (+++) was observed in 6 of 48 OPSCC cases (12.5%) and in 1 of 140 OSCC cases (0.7%). P16 (+++) was significantly higher in OPSCC than in OSCC (P = 0.003). However, in OPSCC, Using P16 (+++) as a marker for HPV DNA infection yielded a sensitivity of 62.5%, Kappa coefficient between HPV DNA and P16 (+++) was 0.67 (P <0.0001). HPV DNA infection and P16 (+++) were not linked to prognosis (DFS: P = 0.35, P = 0.51; OS: P = 0.99, P = 0.96), Moreover, In OSCC, Age, T, N, and clinical stages were correlated with prognosis. Our results indicate that P16 (+++) can act as a biomarker for HPV- related high-risk tumors in OPSCC, yet not in OSCC. Besides, Older patients, less favorable T, N, and clinical stages having a worse prognosis in OSCC. In those with OPSCC, only the younger age of patients was associated with a better prognosis.